Impact of climate change on Ostrinia nubilalis (Lepidoptera: Crambidae) phenology and its implications on pest management - Gagnon, Annie‐Ève; Bourgeois, Gaétan; Bourdages, Line; Grenier, Patrick; Blondlot, Anne (Agricultural and Forest Entomology, 2019)
Abstract Climate change can cause negative impacts to the agricultural sector by increasing pest damage to crops. The European corn borer (ECB) is a major insect pest of corn in North America. Its speed of development could potentially accelerate under a warmer climate, leading to an earlier development of the first generation and an increase in the number of generations per year. The main objective of this study was to assess the potential impacts of climate change on ECB management for the future period 2041–2070 in Quebec, Canada, using bioclimatic modelling and climate analogues. First flight of ECB moths could occur about 15 days earlier in the season in 2041–2070 compared to the reference period 1970–1999. The window for insecticide interventions may be reduced under climate change by 15.6% to 27.8% for univoltine ECB and by 13.8% to 52.7% for bivoltine ECB. Climate change could promote the development of an additional generation in the southern region for both races, considering temperature increases and factors inducing the overwintering diapause. ECB management could become more costly both economically and environmentally under the future climate, and it should be revised according to the results of this study.

The issue of properly ordering climate indices calculation and bias correction before identifying spatial analogs for agricultural applications - Grenier, Patrick; Firlej, Annabelle; Blondlot, Anne; Logan, Travis; Ricard, Marie-Pier (Climate Services, 2019)